Biodegradation of Butachlor by Pseudomonas aeruginosa Strain B2 Isolated From Agricultural Soil (Journal of Environmental Microbiology and Toxicology, 2025)
The chloroacetamide herbicide butachlor (N-Butoxymethyl-2-chloro-2', 6'-diethyl acetanilide) is frequently used to eradicate undesirable weeds from paddy rice, corn, soybean, and other crop plants. Regular use of these pesticides has caused them to persist in soil and water, making them pollutants. As a result, the herbicide must be bio-remediated using an economical and environmentally responsible technique. This study examined the butachlor herbicide in a controlled laboratory setting. The soil was gathered from Gadar Kazaure's agricultural areas in Jigawa State, Nigeria. At 130 rpm and 30 ºC, the soil sample was enriched in Mineral Salt Medium (MSM) with 0.1 mL of butachlor as the only carbon source. After plating the enriched culture, the bacteria that grew the best were separated and designated as GKSS1, GKSS2, and GKSS3. The biodegradation of strains was evaluated at butachlor concentrations of 0.05 mL and 0.1 mL in 120 hours (pH 7.0, 30 ºC). The isolate (GKSS1) demonstrated a degradation efficiency of 75% and 90% at 0.05 mL and 0.1 mL of butachlor, respectively. Pseudomonas aeruginosa strain B2 was determined to be the bacterial isolate GKSS1 by molecular and biochemical analysis. This work is the first to be published on the isolation of bacteria that break down butachlor from the sample collection location.
Keywords: Gadar Kazaure; Pseudomonas aeruginosa; Butachlor; Herbicide; Bioremediation